Effect of pH on the preparation of poly-L-lysine-stabilized calcium alginate beads for immobilization of aminoacylase - Lee, Kong H.; Lee, Pat M. (Kluwer Academic Publishers, 1993)
The preparations of calcium alginate beads stabilized with poly-L-lysine and encapsulating aminoacylase were conducted at different pH conditions. The interaction of poly-L-lysine and alginate beads proceeds readily. The beads prepared at pH 7.0 exhibited high operational and storage stability with the elimination of enzyme leakage and the immobilized aminoacylase possessed high biological activity.